Payment For Environmental Service: An Application in Tourism in Vietnam - Nguyen Van Hieu; Dang Thi Thanh Thuy; Nguyen Hoang Nam (SEAS (Sustainable Environment Agricultural Science), 2020)
Payment for Environment/Ecosystem Services (PES) is a market-based approach toward the dual goal of poverty alleviation and forest conservation. In Vietnam, PES has been nationwide applied to the forest environment, namely Payment for Forest Environmental Services (PFES). Nevertheless, the PFES application in forest-based tourism is very limited. To enhance policy implementation in practice, this study analyses a case study in Sapa town, Vietnam. We find that the overlapping revenue of service providers is a substantial issue holding back PFES applications in tourism. Accordingly, we recommend two potential payers for tourism-PFES, including accommodation companies and ticketing companies (based on the revenue from entrance tickets). We then suggest a PFES payment level of 1 percent of total revenue from ticket sales and room charges. Moreover, the study also provides some recommendations to ensure the fairness and transparency in PES application, as well as factual, reflect of the nature of PFES during implementation.